Structural basis for specific inhibition of the highly sensitive ShHTL7 receptor. (18th July 2018) - Shahul Hameed, Umar; Haider, Imran; Jamil, Muhammad; Kountche, Boubacar A; Guo, Xianrong; Zarban, Randa A; Kim, Dongjin; Al‐Babili, Salim; Arold, Stefan T
Abstract: Striga hermonthica is a root parasitic plant that infests cereals, decimating yields, particularly in sub‐Saharan Africa. For germination, Striga seeds require host‐released strigolactones that are perceived by the family of HYPOSENSITIVE to LIGHT (ShHTL) receptors. Inhibiting seed germination would thus be a promising approach for combating Striga . However, there are currently no strigolactone antagonists that specifically block ShHTLs and do not bind to DWARF14, the homologous strigolactone receptor of the host. Here, we show that the octyl phenol ethoxylate Triton X‐100 inhibits S. hermonthica seed germination without affecting host plants. High‐resolution X‐ray structures reveal that Triton X‐100 specifically plugs the catalytic pocket of ShHTL7. ShHTL7‐specific inhibition by Triton X‐100 demonstrates the dominant role of this particular ShHTL receptor for Striga germination. Our structural analysis provides a rationale for the broad specificity and high sensitivity of ShHTL7, and reveals that strigolactones trigger structural changes in ShHTL7 that are required for downstream signaling. Our findings identify Triton and the related 2‐[4‐(2, 4, 4‐trimethylpentan‐2‐yl)phenoxy]acetic acid as promising lead compounds for the rational design of efficient Striga ‐specific herbicides. Synopsis: The parasitic plant Striga controls its germination through the ShHTL family of proteins that sense the presence of host‐produced strigolactones. This study shows that Triton X‐100 inhibits Striga hermonthica seed germination without affecting host plants by specifically plugging the catalytic site of ShHTL7, the most potent ShHTL member, precluding its structural rearrangements required for downstream signaling. Triton X‐100 and related molecules are promising lead compounds for inhibiting S. hermonthica seed germination without affecting the host plant. The X‐ray structure of ShHTL7 explains how Triton X‐100 precludes structural changes required for downstream signaling. ShHTL7‐specific inhibition by Triton X‐100 demonstrates the dominant role of this particular ShHTL receptor for Striga germination. Abstract : Germination of the parasitic plant Striga depends on ShHTL receptors that sense host‐released strigolactones. This study shows that Triton X‐100 inhibits Striga hermonthica seed germination without affecting host plants by specifically plugging the catalytic site of ShHTL7, thus interfering with downstream signaling.